ANALISA PENGARUH KATALIS TEMBAGA PADA KATALYTIK KONVERTER TERHADAP EMISI GAS CARBON MONOKSIDA DAN HIDRO KARBON PADA KENDARAAN MOTOR BENSIN - ., Mustaqim; Hidayat, Tofik; Nur Hidayat, M. Ginta (ENGINEERING, 2011)
The growth of motor vehicles in Indonesia is quite fast to bring the influence of the increased usage of fuel oil, so that the air pollution becomes inevitable. Motor vehicles are the largest source of pollutant emissions and contribute to the Carbon Monoxide of the pollutants that exist, where from year to year pollution levels increased along with the increasing use of motor vehicles. One of the things that can be done by researchers in this application is the installation of emission control teknology Catalytic Converters are installed in the exhaust gas channel. Catalytic Converter generally use this type of expensive metal catalysts and rare in the market (Palladium, Platinum and Rhodium). Based on the fact above, so we do by making